Supply Disruptions and Optimal Network Structures - Bimpikis, Kostas; Candogan, Ozan; Ehsani, Shayan (Management Science, 2019)
This paper studies multitier supply chain networks in the presence of disruption risk. Firms decide how much to source from their upstream suppliers so as to maximize their expected profits, and prices of intermediate goods are set so that markets clear. We provide an explicit characterization of (expected) equilibrium profits, which allows us to derive insights into how the network structure—that is, the number of firms in each tier, production costs, and disruption risk—affect firms’ profits. Furthermore, we establish that networks that maximize profits for firms that operate in different stages of the production process—that is, for upstream suppliers and downstream retailers—are structurally different. In particular, the latter have relatively less diversified downstream tiers and generate more variable output than the former. Finally, we consider supply chains that are formed endogenously. Specifically, we study a setting where firms decide whether to engage in production by considering their (expected) postentry profits. We argue that endogenous entry may lead to chains that are inefficient in terms of the number of firms that engage in production. This paper was accepted by Vishal Gaur, operations management.